2005
DOI: 10.1536/ihj.46.167
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Increase in Right-to-Left Shunt After Acute Myocardial Infarction in a 68-year-old Male With Tetralogy of Fallot

Abstract: SUMMARYA male patient with tetralogy of Fallot accompanied by aortic regurgitation had maintained sufficient exercise capacity for a number of decades with the status of acyanotic tetralogy of Fallot. When he was 67 years old, he suffered a posterior wall acute myocardial infarction and direct percutaneous coronary angioplasty successfully revascularised the target lesion in the left circumflex artery. However, a few months after the onset of the myocardial infarction, his shortness of breath became clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Izawa at al. reported an AMI case with uncorrected TOF and that had a critical increase in right-to-left shunt in the period after AMI [2]. In our case, echocardiography after the second AMI event showed an increase in right-to-left shunt and a decrease in Qp/Qs ratio as compared with after the first AMI event (from 1.18 to 1.0), the same as in Izawa's report [2].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Izawa at al. reported an AMI case with uncorrected TOF and that had a critical increase in right-to-left shunt in the period after AMI [2]. In our case, echocardiography after the second AMI event showed an increase in right-to-left shunt and a decrease in Qp/Qs ratio as compared with after the first AMI event (from 1.18 to 1.0), the same as in Izawa's report [2].…”
Section: Discussionsupporting
confidence: 84%
“…reported an AMI case with uncorrected TOF and that had a critical increase in right-to-left shunt in the period after AMI [2]. In our case, echocardiography after the second AMI event showed an increase in right-to-left shunt and a decrease in Qp/Qs ratio as compared with after the first AMI event (from 1.18 to 1.0), the same as in Izawa's report [2]. Dabizzi et al reported that 36% of TOF cases were associated with anomalies in coronary course or/and distribution, and sometimes had enlarged conus branch or aberrant vessel crossing over the RVOT [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications have reported coronary artery disease in patients with or without repair for tetralogy of Fallot [1421]. Whether the risk of developing coronary heart disease is higher in patients with tetralogy of Fallot than in the general population is unknown [16]. For sure, tetralogy of Fallot was one of the first complex heart defects with which patients could survive beyond the fourth decade of life.…”
Section: Introductionmentioning
confidence: 99%